The challenges and treatment of abattoir effluents: a South African perspective. Issue 12 (18th November 2022) - Moreroa, Mabatho; Basitere, Moses
Abstract: South Africa's (SA's) water resources have been severely affected by the demand for meat products. The growing population has resulted in an increase in food production, increasing the number of abattoirs from 25 in 1988 to 420 in 2021. Organic matter is abundant in abattoir effluent, with chemical oxygen demand levels reaching 9, 000 mg/L. To reach permissible discharge limits, various methods such as sequential bed reactor, granular sludge bed, membrane bioreactor, and membrane filtration have been adopted. However, some abattoirs do not meet municipal regulatory requirements. As a result, practical and cost-effective approaches such as biofilm reactors were developed to encourage abattoirs to employ water treatment technology. Bioreactor-based technologies have proven to be successful, with more than 90% efficiency. Fat, oil, and grease (FOG) are problematic in abattoir effluents as they emit odours, attract insects, and impair the biodegradability of wastewater. For this reason, hydrolysis using a novel agent (Eco-flush ™ ) has shown to be an effective technique for decreasing FOG. During treatment, biogas produced by anaerobic degradation may be utilized as an energy source to alleviate SA's energy problem. This review aims to outline the challenges related to abattoir wastewater in SA and highlight the gaps associated with abattoir wastewater treatment. HIGHLIGHTS: The study considers hydrolysis of solids arising from abattoir effluent. Production of biogas from anaerobic digestion of abattoir effluent is studied. Bioremediation of abattoir effluents using a biofilm reactor is studied. The South African abattoir industry is analysed critically. Integrated treatment systems for the bioremediation of abattoir effluents are suggested. Graphical Abstract